The effects of alley cropping with Leucaena leucocephala and of different management practices on the productivity of maize and soil chemical properties in lowland coastal Kenya - Mureithi, J.G.; Tayler, R.S.; Thorpe, W.R. (Springer, 1994)
The effects of leucaena hedgerows, mulching with leucaena foliage (0.50 and 100 percent of harvested foliage), cowpea intercropping and addition of dairy cattle slurry (55 t ha-1 per maize crop) on the yield of maize from a sandy soil were assessed. The four-year results from five maize crops are reported. Except in the first year, yields of maize grain and stover were significantly reduced by 30 percent in the presence of leucaena hedgerows. Use of leucaena mulch eliminated this effect; application of all the harvested leucaena mulch (100 percent) increased the total maize grain yield of the five crops by 44 percent over sole maize. hedgerow and mulching management required an additional 36 mandays labour ha-1 which was more than compensated by the increased maize yields. Furthermore leucaena hedgerows substantially depressed the growth of weeds between cropping seasons. Intercropping with cowpea significantly depressed yields of maize grain and stover when both crops were sown together, but not in later seasons when cowpea was sown four weeks after the maize. application of slurry increased the total yields of maize grain and stover by 35 and 37 percent, respectively. The grain yield of maize in leucaena hedgerow treatments fertilized with slury did not respond to application of more than 50 percent of leucaena foliage, which suggested that half of the foliage could be spared for feeding to livestock. The cumulative yield of maize grain from the highest yielding organic system was 85 percent of the yield from the fertilizer treatment. The study, which is continuing, demonstrates that large increases in agricultural productivity are possible through the intercropping of maize with woody forage and grain legumes and the integration of dairy cattle production into the system. It thus shows the importance of exploiting crop/livestock interactions.